Together on the way to the monastic church of Mīt Damsīs: Copts and Muslims at the mūlid of Saint George in medieval Islamic Egypt and beyond. Issue 2 (2nd April 2016) - Wissa, Myriam
ABSTRACT: Pilgrimage was a common practice in pre-Islamic and medieval Islamic times. A number of Christian shrines, churches, and monasteries, particularly those associated with the Holy Virgin Mary and Saint George, hosted Muslim visitors. Every year, both Christians and Muslims would gather to celebrate a saint's feast. Whilst Bukhārī's sahīh and several Islamic legal treatises banned this bida' (innovation), the practice of Muslim pilgrimage to non-Muslim sites has vividly survived in the modern and contemporaneous Middle East. Exploring the ways in which historical events intersect with social practices, this article examines the religious and communal adaptation of the church-monastery of Saint George at Mīt Damsīs, located on the East Bank of the Nile in Northern Egypt. It looks at the mixing of both Muslims and Christians in the festival of Saint George and shows its spiritual dimension. The article finally demonstrates how Mīt Damsīs is representative of a distinct model of veneration and pilgrimage identity, and how individual Muslims' piety in medieval Islamic Egypt and beyond embraced the concept of the divine origins of Judaism, Christianity, and Islam.